Pemanfaatan Game Edukatif MathPlayground untuk Melatih Keterampilan Berhitung Siswa Diskalkulia - Annisa Shafa Az Zahra; Tatag Yuli Eko Siswono (MATHEdunesa, 2026)
Counting skills are an important basic ability for every student, including for students with learning disabilities such as dyscalculia. However, in reality, less interactive learning methods at school are often an obstacle, so that students with dyscalculia have difficulty in developing their counting skills. The low level of numeracy skills requires innovation in the learning process. One of the alternative solutions used in this research is the utilization of MathPlayground educational games, which are designed to provide a learning experience that is more interesting, interactive, and in accordance with the needs of students with dyscalculia. This study aims to describe the counting skills of grade VI elementary school students with dyscalculia before and after using the MathPlayground educational game Jet Ski Addition, and to find out their responses to the use of the game. This research uses a qualitative approach with the type of case study research on four subjects of dyscalculia students at SD Negeri 2 Taman Madiun City. Data collection techniques were carried out through dyscalculia tests, early and late counting skills tests, observations, and interviews. The data analysis technique uses the standard value of book adaptation for dyscalculia tests, counting skills test indicators, recording observations, and data reduction of interview results. The results showed that before the intervention, students experienced obstacles in the counting process such as lack of understanding of the problem, slow calculation strategies, and low levels of accuracy and concentration. After being given an intervention through the Jet Ski Addition educational game from MathPlayground, students' counting skills improved both in the thinking process, time efficiency, and accuracy of answers. In addition, students showed a positive response to the game which was considered fun, challenging, and able to foster learning motivation.